Penilaian Hubungan Kadar Hemoglobin Darah terhadap Kemampuan Working Memory pada Siswa SMA - Sidrah Nadira, Cut; Sri Rahayu, Mulyati; Maulina, Nora; Muhammad, Oktaduta; Akbar, Rizki (Jurnal Ilmiah Manusia Dan Kesehatan, 2023)
Memory is a person's ability to store information that can be recalled for later use. There are several factors that can affect a person's memory, namely, age, gender, physical activity and sports, stress and depression, environmental conditions, and nutrition. Lack of hemoglobin levels that occur continuously for a long time will cause children to experience cognitive disorders, hearing disorders, vision disorders, emotional disorders, hyperactivity, difficulty receiving and processing information, and forgetfulness, thus hampering the child's learning process and having an impact on low memory and decreased performance. The purpose of this study was to determine the characteristics of students, determine hemoglobin levels in students, determine the level of working memory in students and determine the relationship between hemoglobin levels and working memory in students of SMA Negeri 1 Samudera, North Aceh Regency. The design of this research is research using this research is an analytic study of 150 students. The research design used was a cross-sectional study statistical analysis using chi-square. The results show that most of the hemoglobin levels of SMA Negeri 1 Samudera students are in a low category, most of the working memory of SMA Negeri 1 Samudera students are in a good category, and there is a relationship between hemoglobin levels and working memory in SMA Negeri 1 Samudera students.